Improving local land governance? Exploring the linkages between land governance reforms, institutional pluralism and tenure security in Burundi. Issue 1 (2nd January 2018) - Tchatchoua-Djomo, Rosine
ABSTRACT: Reforms in land governance are assumed to significantly enhance the security of tenure in conflict-affected countries, through stimulating the resolution of land disputes, contributing to better control of property rights and reorganising the institutional framework for land management. Yet, this paper highlights the ambiguous outcomes of such reforms in situation of institutional multiplicity. Fieldwork in Ngozi province in northern Burundi points out how land-related reforms such as decentralising the administrative authority at the communal and hill levels and policy reforms in the formalisation of property rights have positive impacts in terms of dealing with specific land disputes and fostering local feelings of tenure security in the aftermath of the 2000 Arusha Peace Agreement. However, land governance reforms have also fuelled the proliferation of land governing institutions and fostered confusion among state and non-state authorities about which rules to apply and their roles in mitigating tensions over landownership and enforcing property rights. Actually, while introducing new laws, policies, institutions and practices, land governance reforms have produced mixed effects in securing local tenure for most community members and increased contestations against the authority of government representatives at the local level.